To Evaluate Importance of Coagulation Factors and Septic Screen Parameters in Prognosis of Surgical Necrotizing Enterocolitis - Tinwala, Hafeza Nazimhusein; Gupta, Pradeep; Kumar Chopda, Ashok; Kumar Khare, Atul (Journal of Neonatal Surgery, 2025)
Background: Necrotizing enterocolitis is an ongoing acquired inflammatory disease condition affecting the entire gut especially during the neonatal period, particularly preterm and low birth weight infants. NEC is notorious for its rapid onset, diagnostic challenges, and high mortality rate, posing a severe threat to neonatal life. Aims-Relating parameters of coagulation and septic screen at the time of NEC diagnosis undergoing different surgical interventions and its applicability in further prognosis and outcome. Methods and materials: A prospective observational study done in the department of pediatrics surgery, SMS Medical college Jaipur, in 70 patients from April 2023 to April 2024 with patients living between day1 to live day 28 were included. All had preoperative clinical -radiological features consistent with NEC and with intraoperative findings of NEC, were initially resuscitated, were taken a detailed history with demographic data and investigated with baseline and specific coagulation profile and sepsis screen and then were operated. An analysis of outcome and prognosis was done based on altered specific/predictive parameters taken into consideration. Results: a total of 70 patients that underwent surgical procedure it was found that not only platelets count, but PT INR, APTT, CRP and D-DIMER were independently associated with surgical NEC. APTT and D-DIMER could be identified raised high significantly in poor prognostic neonates with 90 % specificity, 91 % sensitivity and 54.50% specificity 68.6% sensitivity respectively. Coagulopathy was found in almost 90% of cases of surgical NEC and 92% of those dyed to NEC. Conclusion: Coagulation profile and septic screen parameters at the time of surgical NEC, are facilitative in predicting poor prognosis and likely deaths related to NEC. Hence, they should be scrutinized closely and can be used in future as conducive decision-making tools of surgical management and predict whether the outcome would be bad or good irrespective of intervention.